Effectiveness of Aloe Vera-Based Topical Therapy Products on Breastfeeding Mothers with Milk Scratches in Hamparan Perak Village - Arma, Nuriah; Harahap, Novy Ramini; Wulan, Mayang; Firnanda, Yuka Okta (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
In Indonesia, a study revealed that approximately 86.4% of breastfeeding mothers encounter nipple issues such as blisters, dryness, and pain. The World Health Organization (WHO) emphasizes that chafed nipples contribute to substantial pain, discomfort, and diminished milk production among nursing mothers, thereby posing a hindrance to exclusive breastfeeding initiatives. This study aims to investigate the effectiveness of an aloe vera-based topical therapy product in reducing nipple chafing in breastfeeding mothers in Hamparan Perak District. Conducted as an experimental study with a pre-test and post-test control group design, the research transpired in Hamparan Perak village. The study enlisted breastfeeding mothers experiencing sore nipples, with 20 individuals in the intervention group receiving aloe vera-based topical therapy in gel form, and 20 individuals in the control group receiving a placebo. The assessment of effectiveness centered on measuring blister occurrence and nipple pain scores both before and after the intervention, employing the Mann-Whitney test for data analysis. Bivariate analysis utilizing the Mann-Whitney U-test yielded a significant P-value of 0.001. Consequently, it can be inferred that aloe vera gel demonstrably influences nipple pain, with aloe vera gel proving to be 5,537 times more effective in pain reduction. Future research could incorporate objective measures, such as clinical assessments or laboratory analyses, to validate the reported outcomes.